PRINCIPLES OF OFFICIALITY AND PUBLICITY IN REGISTRATION ACTIVITIES OF THE UKRAINIAN MINISTRY OF JUSTICE - Serhiy, Mykytiuk (SUPREMANCE OF LAW, 2018)
’1 he research of the principles of registration is essential for both theory and practice as they are the guiding ideas that characterize the content of the registration, as well as its separate stages and institutions, with their help the result of registration and legality is provided.